Social Activities of SNDP Yogam Praveen O.K (LPC Bulletin on Research, 2011)
Sree Narayana Guru was one of the epoch making sees of the present century, who has dynamically effected a radical change in the social, moral and spiritual value, vision and behavioral patterns of his contemporaries in India. Among the socio-religious reformers of modern India who clamored for social justice, the name of Sree Narayana Guru occupies a permanent place. His life and mission brought out far reaching changes in the year 1854 A.D at Chempazhanthi, in the suburb of the city of Trivandrum. He has not received this aura of worldwide attention, although he was also one of those in the socio-religious reformers and Gurus in South India, especially in and around Kerala. He was an embodiment of all that is good in human life. The impact of the activities of Sree Narayana Guru is so varied that it has reflected the whole Kerala in the field of education, society, religion, economy, politics and culture. In 1903 he founded [Sree Narayana Dharmma Paripalana Yogam (SNDP)].